Breathing Patterns and Oxygenation Saturation During Sleep in Children Habitually Living at High Altitude in the Andes: A Systematic Review - Santiago Ucrós; Javier A. Castro-Guevara; Catherine M. Hill; Jose A. Castro-Rodriguez (Frontiers Media S.A., 2022)
BackgroundHuman respiratory physiology changes significantly in high altitude settings and these changes are particularly marked during sleep. It is estimated that 170 million people live above 2,500 m in environments where normal sleep parameters differ from those established at sea level or low altitude.MethodsWe conducted a systematic review of publications reporting sleep studies in healthy children living at high altitude. For this purpose, data from PubMed, EMBASE, SciELO and Epistemomikos bases were retrieved up to August 2021.ResultsSix articles met specified inclusion criteria; all reporting data were from South America involving 245 children (404 sleep studies) in children aged 0.6 months to 18 years, at altitudes between 2,560 to 3,775 m. The main results were: (1) Central apnea index decreased as the age increased. (2) The obstructive apnea/hypopnea index showed a bimodal profile with an increase in young infants up to age of 4 months, decreasing to 15 months of age, and then a second peak in children aged 4 to 9 years of age, dropping in older schoolchildren and adolescents. (3) Periodic breathing in the first months of life is more marked with increasing altitude and decreases with age.ConclusionsThere are few studies of sleep physiology in children living at high altitude. The international parameters defining normal apnea indices currently used at low altitude cannot be applied to high altitude settings. The interpretation of sleep studies in children living at high altitude is complex because there are important developmental changes across childhood and a wide range of altitude locations. More normative data are required to determine thresholds for respiratory pathology at a variety of high altitude settings.